Financial Performance Analysis of Bank Syariah Indonesia Post Merger: RGEC Approach - Ningsih, Setia; Hendra H. Dukalang (Department of Islamic Banking, 2024)
Bank is a company that has an important role in building the economy. In Indonesia, commercial banks used by the public are Conventional Banks and Islamic Banks. One important factor that shows the efficiency and effectiveness of Islamic banking in achieving its goals is performance. The occurrence of a continuous decline in performance can cause the bank to be in a bad state, even at risk of bankruptcy and loss of trust from customers. As a newly merged bank, Bank Syariah Indonesia (BSI) needs to measure the health level of the bank. This study aims to measure the health level of BSI using the RGEC method (Risk Profile, Good Corporate Governance, Earning and Capital). The results of data analysis and discussion show that the assessment of the health level of BSI from 2021 to 2022 using the RGEC method (Risk Profile, Good Corporate Governance, Earning and Capital) as a whole can be said that BSI is a very healthy bank.